From Identity to Representation: Ibn Sīnā on the Identity of Knower and Known in the Human Rational Soul - İbrahim Halil Üçer (Nazariyat: Journal for the History of Islamic Philosophy and Sciences, 2018)
The question of what sort of a relation the human rational soul has with the object of thought in the course of actual intellection is one of the major problems of Avicenna’s epistemology. On this question, Avicenna inherited a wide range of interpretations around the theory of the identity of intellect and intelligible that was introduced in De Anima 3.4 by Aristotle. This study aims to establish the final position of Avicenna with respect to this theory. However, there are certain difficulties in determining his original view and final position on this issue. In his early work al-Mabdaʾ wa-al-maʿād he accepts the position of identity, yet in the later al-Shifāʾ/al-Nafs and al-Ishārāt, he sharply refutes a similar stance that he attributed to Porphyry, though the real opponent remains unacknowledged, and holds the opinion of the immaterial representation of the intelligibles. Yet again, he still uses a language of unity (ittiḥād) in the works posterior to al-Shifāʾ/al-Nafs. In order to solve this apparent inconsistency and determine the real view of Avicenna, this article offers an aporetic reading of relevant passages in Avicenna’s works. For this reading, Avicenna held the view of identity in al-Mabdaʾ where he lacked a distinction between the direct self-awareness and indirect self-intellection. However, from on al-Shifāʾ/al-Nafs in which he set the ground for this distinction he moved on to the theory of representation and kept at this attitude consistently in later works. The questions of, what is the location of Avicenna’s theory of representation in the history of problem, and the possible identity of the real opponent or opponents to whom Avicenna attributed Porphyrian position form the other points that this article is concerned with.